Pinna of ear: a potential biometric identifier - M., Maitreyee (International Journal of Research in Medical Sciences, 2017)
Background: Individual differences in morphometric and somatoscopic observations of pinna of ear were studied to explore the potential of pinna of ear as a biometric tool. Methods: Morphometric and somatoscopic data of right ear of 350 Indian individuals (Age: 17-25 years) was collected. Measurements of pinna length, pinna width, pinna root, pinna projection, intertragic distance, ear lobe length, and ear lobe width were taken. Observations were done for presence or absence of Darwin tubercle, flat or rolled helix, and attached or free ear lobe. Probability statistics was extrapolated to assess the variations in ear pinna characters. Results: All measurements showed a wide range. There was statistically significant difference between male and female pinna measurements. The somatoscopic observations showed 82.9% individuals with presence of Darwin tubercle, 99.1% with rolled helix, and 65.4% with free ear lobes. On the basis of extrapolation of ten different morphometric and somatoscopic parameters, the statistics showed the probability of any two individuals having exactly same observations to be 0.0008%. Conclusions: The wide range of measurements in the present study suggested a high possibility of variations amongst the population. If all the parameters including both morphometric and somatoscopic, are taken into consideration, the pinna of ear of each individual is a very distinctive structure, which makes it a potential biometric identifier and with the use of proper technologies, it will be a widely used biometric tool in the future.